TRANSFORMATIONAL LEADERSHIP, A SUCCESSFUL MODEL FOR ORGANIZATIONS IN LEADERSHIP STYLES - Boushra WAKED NAJAR (Annals of the University of Oradea: Economic Science, 2023)
The issue of leadership as a phenomenon began in the 19th century and we even witness an earlier theory from 1885-1795 that was developed by the historian Thomas Carlyle, he called it the "Great Man" theory .This theory represents the leader as a different person from the rest of mortals, because this theory saw the leader as a messenger bearing the good news. And that he has the capacity and ability in his personality to shape the masses and turn them into society (the full range model of leadership. Leaders who have the capacity for leadership and action are the ones who will succeed in reaching the potential of the organization or society. From this theory arose another called the "trait approach" because it described the leader as a person with exceptional qualities. Later in the 1940s, the theory called "the situational approach" was developed. This theory focused on the behavior of the leader and not on his qualities, but this approach had drawbacks, like, if the leader is not able to shape himself then how can he motivate his people in his organization. That is why the search began for a strong model in leadership, which does not follow or according to the situation. Look for a theory that will have a character that will present its goals clearly, a theory that on the one hand can lead and promote the customs to the goals of the organization and on the other hand it shapes the situation. This model is expressed in the name " Transformational leadership" according to Burns 1978. Although there are many definitions of leadership, the principles of leadership in organizations are focused on the execution and promotion of processes whose principle and purpose are to lead in the design and determination of policy and its implementation. These processes include planning, defining procedures, building a vision and making decisions. This chain of events is also used by the road leader in motivating and leading his followers and encouraging them, because he instills in them the belief in their high ability. The leader always makes sure to act together in order to achieve a common goal (Bass 1990, Stogdill 1950, Bryman 1996, House 1971) and to solve problems together and not to rely on the skills of individuals, therefore the focus of leadership is on empowerment and not on control.